FOOD SECURITY STATUS AND IMPACT OF CLIMATE SMART PRACTICES ON MAIZE PRODUCTIVIVITY IN ADAMAWA STATE, NIGERIA: A PROPENSITY SCORE MATCHING APPROACH - Ibrahim, H.O.; Wahab, M.J.; Ibrahim, A.A.; Bakare, A.H. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the food security and impact of climate smart practices maize productivity using a propensity matching approach. The specific objectives were to; describe the socio-economic characteristics of maize farmers; assess the food security status, estimate the costs and returns from maize production, determine the impact of climate smart practices on output and income, and describe the constraints faced by maize farmers in the study area. A multi stage sampling techniques was employed to select 206 maize farmers for the study. Data were collected using well-structured questionnaires and analysed using descriptive statistics, household dietary diversity score (HDDS), gross margin analysis, and Propensity matching score (PSM). The results shows that maize production was male dominated (66.99%), access to formal education (83.50%), active productive age (36.90%), and well experienced. The intercropping with legumes (94.0%) was the most common climate practices among maize farmers in the study area. The result shows that majority (81.0%) of the maize farmers in the study area have good dietary diversity score, which implies that most of them were food secured. Maize production was profitable in the study area with the return on investment of 3.32. The study concludes that adoption of climate smart practices among maize farmers is capable of increasing their productivity in terms of output and income and also resulted to favourable food security level in the study area. There is a need for extension agents to guide farmers on the best periods to cultivate maize and right climate smart practices to adopt in the study area.